Enabling Environment Assessment for Scaling Up Sanitation Programs : Madhya Pradesh, India - Robinson, Andy (World Bank, Washington, DC, 2014)
The Water and Sanitation Program (WSP) is in the start-up phase of a new Global Scaling up Sanitation Project. The project is applying Total Sanitation and Sanitation Marketing (TSSM) to stimulate and scale up sanitation demand and supply. One of the central objectives of the project is to improve sanitation at a scale sufficient to meet the 2015 sanitation Millennium Development Goal (MDG) targets in Indonesia, Tanzania, and the Indian states of Himachal Pradesh and Madhya Pradesh. The baseline enabling environment assessment was carried out during the start-up phase of the overall project in May and June 2007. A follow-up assessment will be carried out at the end of project implementation in approximately May or June 2009. The main objective of this assessment was to establish a baseline of the programmatic conditions needed to scale up, sustain, and replicate the Total Sanitation and Sanitation Marketing (TSSM) approaches in the Indian states of Himachal Pradesh and Madhya Pradesh.